Cho a^2(b+c)=b^2(a+c)= 2018. Tính P = c^2(a+b)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a^3+b^3=c\left(3ab-c^2\right)\Rightarrow a^3+b^3+c^3-3abc=0\)
\(\Rightarrow\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)=0\)
\(\Rightarrow\left(a+b+c\right)\left[2a^2+2b^2+2c^2-2ab-2bc-2ca\right]=0\)
\(\Rightarrow\left(a+b+c\right)\left[\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2\right]=0\)
\(\Rightarrow\orbr{\begin{cases}a+b+c=0\left(loai\right)\\a=b=c\end{cases}}\)
Mà a + b + c = 3 nên a = b = c = 1
Khi đó \(A=672.\left(1+1+1\right)+2=672.3+2=2018\)
a2+b2+c2=ab+bc+ca
<=>2a2+2b2+2c2=2ab+2bc+2ca
<=>(a2-2ab+b2)+(b2-2bc+c2)+(c2-2ca+a2)=0
<=>(a-b)2+(b-c)2+(c-a)2=0
<=>a=b=c
mà a+b+c=3<=>a=b=c=1
=>P=0
\(P=\left(b^2c+abc\right)\left(a^2b+abc\right)\left(c^2a+abc\right)\)
\(=bc\left(a+b\right)\cdot ab\left(c+a\right)\cdot ca\left(b+c\right)\)
\(=\left(abc\right)^2\left(a+b\right)\left(b+c\right)\left(c+a\right)\)
Lại có:
\(\left(a+b+c\right)\left(ab+bc+ca\right)-abc=0\)
\(\Leftrightarrow\left(a^2b+abc+a^2c\right)+\left(ab^2+b^2c+abc\right)+\left(bc^2+c^2a+abc\right)-abc=0\)
\(\Leftrightarrow a^2b+ca^2+ab^2+2abc+ac^2+b^2c+bc^2=0\)
\(\Leftrightarrow a^2\left(b+c\right)+a\left(b^2+2bc+c^2\right)+bc\left(b+c\right)=0\)
\(\Leftrightarrow a^2\left(b+c\right)+a\left(b+c\right)^2+bc\left(b+c\right)=0\)
\(\Leftrightarrow\left(b+c\right)\left(a^2+ab+ca+bc\right)=0\)
\(\Leftrightarrow\left(b+c\right)\left[a\left(a+b\right)+c\left(a+b\right)\right]=0\)
\(\Leftrightarrow\left(b+c\right)\left(a+b\right)\left(c+a\right)=0\)
\(\Rightarrow P=0\)